Clinical Cases in Phototherapy - Koo, John; Nakamura, Mio (Springer International Publishing : Imprint: Springer, 2017)
This case book will be based on real life scenarios of patient cases which have been encountered over several decades in one of the largest phototherapy centers in the United States. To our knowledge, there has not been anything similar published to date. By presenting various cases and how to manage such cases, we aim to educate dermatology trainees and practicing dermatologist who are trying to familiarize themselves with phototherapy. A recent study has shown that many dermatologists do not know how to administer phototherapy, and most graduating residents do not have adequate teaching and experience with administering phototherapy during their residencies. Therefore, the hope is that this book will fill a critical gap in the field of dermatology.
Keywords: Medicine.; Dermatology.; elektronické knihy; electronic books